2014
DOI: 10.1021/pr501003q
|View full text |Cite
|
Sign up to set email alerts
|

A New Workflow for Proteomic Analysis of Urinary Exosomes and Assessment in Cystinuria Patients

Abstract: Cystinuria is a purely renal, rare genetic disease caused by mutations in cystine transporter genes and characterized by defective cystine reabsorption leading to kidney stones. In 14% of cases, patients undergo nephrectomy, but given the difficulty to predict the evolution of the disease, the identification of markers of kidney damage would improve the follow-up of patients with a higher risk. The aim of the present study is to develop a robust, reproducible, and noninvasive methodology for proteomic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…The largest fraction of differentially abundant urinary extracellular vesicle phospholipids identified were lysophospholipids, phosphatidic acid, phosphatidylcholine and phosphatidylethanolamine. In a second study 119 , a combined proteomics and lipidomics analysis of urinary extracellular vesicles from healthy individuals and patients with cystinuria was carried out. Whereas the proteomics analysis detected a pattern of robust differences in the abundance of proteins between the healthy individuals and the patients with cystinuria, the lipidomics analysis was less conclusive.…”
Section: Urinary Extracellular Vesicle Lipidomementioning
confidence: 99%
“…The largest fraction of differentially abundant urinary extracellular vesicle phospholipids identified were lysophospholipids, phosphatidic acid, phosphatidylcholine and phosphatidylethanolamine. In a second study 119 , a combined proteomics and lipidomics analysis of urinary extracellular vesicles from healthy individuals and patients with cystinuria was carried out. Whereas the proteomics analysis detected a pattern of robust differences in the abundance of proteins between the healthy individuals and the patients with cystinuria, the lipidomics analysis was less conclusive.…”
Section: Urinary Extracellular Vesicle Lipidomementioning
confidence: 99%
“…In fact, exosomes have come to the forefront in the nephrology community due to their potential for accessible biomarker discovery [18,24] of renal disease and injury. A recent high-resolution mass spectrometry proteomic analysis of urinary exosomes in cystinuria revealed the role of inflammation in this disease [25]. In-depth proteomic analysis and EM of individual urinary exosomal samples showed that exosomes are innate immune effectors that contribute to host defense within the urinary tract.…”
Section: Characteristicsmentioning
confidence: 99%
“…Lacroix et al studied the urine supernatant proteome of the newborns with obstructive nephropathy and quantified 970 proteins 14. Bourderioux et al studied urinary exosomes derived from patients with cystinuria and identified 1,794 proteins 49. The protein ID overlaps were 48% (compared to Santucci's study) and 78% (compared to the other studies).…”
Section: Resultsmentioning
confidence: 99%